Kakuriyo : bed & breakfast for spirits. 8 - Yuma, Midori; Ioka, Waco (Shojo beat manga., 2023)
"Aoi Tsubaki inherited her grandfather's ability to see spirits--and his massive debt to them! Now she's been kidnapped and taken to Kakuriyo, the spirit world, to make good on his bill. Her options: marry the head of the inn her grandfather trashed, or get eaten by demons. But Aoi isn't the type to let spirits push her around, and she's determined to redeem her grandfather's IOU on her own terms! Aoi is excited about her chance to finally try the famous Tenjin-ya kaiseki meal and stay the night in one of the inn's lavish rooms. But unexpected guests throw the staff into an uproar and send Aoi and the hot springs manager fleeing into the night. What mystery has arrived at the Demon's Gate while the Ōdanna is away?"--Provided by publisher.